2021
DOI: 10.5812/ans.117199
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Daily Living of Patients with Spinal Cord Injury: A Cross-Sectional Study in Kermanshah

Abstract: Background: Spinal cord injuries (SCI) are a variety of chronic diseases that various causes such as trauma may contribute to its onset. One of the problems in these patients is the problem of physical activity and, consequently, daily activities. Objectives: This study aimed to assess daily living of patients with SCI. Methods: In this descriptive cross-sectional study in 2019, 120 patients with SCI in Kermanshah were included in the study using purposive sampling. The instruments used in this study fell into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…All of the ten studies (30,31,32,33,34,35,36,37,38,39) reported that the maximum level of participation in daily life activities among persons with SCI in the community like employment, return to work, engagement in primary life domain, leisure activities, outdoor work, household duties, community mobility, driving task, and self-care activities are affected. Meanwhile, white-collar paid or unpaid work, hobbies, and sporting activities are the facilitator factors that contribute to participation in the community.…”
Section: Activity and Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the ten studies (30,31,32,33,34,35,36,37,38,39) reported that the maximum level of participation in daily life activities among persons with SCI in the community like employment, return to work, engagement in primary life domain, leisure activities, outdoor work, household duties, community mobility, driving task, and self-care activities are affected. Meanwhile, white-collar paid or unpaid work, hobbies, and sporting activities are the facilitator factors that contribute to participation in the community.…”
Section: Activity and Participationmentioning
confidence: 99%
“…Personal Factors: Seven studies (30,31,34,35,37,38,39), reported that participation of persons with SCI in daily activities after being discharged from the hospital to home face many obstacles due to personal factors such as dependency on caregivers, older age status, gender, aloneness, less qualified. Meanwhile, social background, financial support, lifestyle, coping, and life satisfaction are the primary facilitator factors that enhance their participation in work and independent life in society.…”
Section: Activity and Participationmentioning
confidence: 99%
“…The SCI is defined as damage to the spinal cord that results in the loss of sensory, motor, or autonomic function (6). These complications might lead to problems, such as pain, pressure ulcers, psychological problems, care stress, and reduced physical activity (7)(8)(9). The SCI is one of the chronic diseases that cause caregiver burden in healthcare providers (10).…”
Section: Introductionmentioning
confidence: 99%